Kesehatan Gigi Sangat Penting untuk Anak Usia sekolah - Nita Theresia; Fetty Rahmawaty; Ester Inung Sylvia; Aldian Yusup (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – Toothache in children is a common problem and is felt by children who experience continuous aching teeth. Types of dental problems such as cavities, brittle teeth, are caused by the habit of eating chocolate, candy and not brushing your teeth regularly. In addition to toothache, children also experience abnormalities in the mouth, such as bad breath due to rotten teeth. The event of toothache in children begins when the child begins to grow his teeth perfectly. Range at the age of 1.5 - 6 years. The process of child growth and development has formed a flat tooth arrangement. If at the age of golden age children do not get regular, healthy and proper dental care, it will have an impact on the strength of the teeth in their teens to adulthood. The purpose of this study is to provide understanding and prevention as well as appropriate actions for dental care in children. This research methodology uses a qualitative approach to literature study design. The results of the study explained that the habit of brushing teeth properly and appropriately needs to be given training for children. The role of medical personnel in realizing the healthy teeth movement program for children provides an opportunity for schools to become partners in the children's healthy teeth program regularly every 6 months. Collaboration between dentists, schools and parents can be realized consciously and planned.